2006
DOI: 10.1097/01.ccm.0000201400.63304.41
|View full text |Cite
|
Sign up to set email alerts
|

Four methods of measuring tidal volume during high-frequency oscillatory ventilation

Abstract: Tidal volume can be measured during high-frequency oscillatory ventilation using a variety of techniques. Frequency-specific calibration improves the accuracy and precision of tidal volume measurements. Hot wire anemometry exhibits stable performance characteristics across the range of temperature, humidity, Fio2, and inspiratory/expiratory ratios encountered clinically, has a small deadspace, is unaffected by mean airway pressure, and is therefore suitable for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Furthermore, due to rigid enrollment criteria that prohibited the study of patients requiring vasopressors or those in whom PAW was Ͼ35 cm H 2 O, our patients tended to be those who were recovering and approaching transition back to conventional mechanical ventilation. Last, placement of the HW between the ETT and Y-connector of the 3100B reduces delivered VT by approximately 13% across all settings (10). The VTs we have reported therefore underestimate by a small amount what would actually be delivered.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Furthermore, due to rigid enrollment criteria that prohibited the study of patients requiring vasopressors or those in whom PAW was Ͼ35 cm H 2 O, our patients tended to be those who were recovering and approaching transition back to conventional mechanical ventilation. Last, placement of the HW between the ETT and Y-connector of the 3100B reduces delivered VT by approximately 13% across all settings (10). The VTs we have reported therefore underestimate by a small amount what would actually be delivered.…”
Section: Discussionmentioning
confidence: 83%
“…Volume measurements were corrected in real-time using frequency, I:E ratio, and ETT internal diameter-specific calibrations. In a previous study, we demonstrated that these calibrations improve the accuracy of this device (mean error of Ϫ1.1%; 95% confidence interval, Ϫ5.5% to 3.3%) across a wide range of 3100B settings (f, 3-12 Hz; ⌬P, 30 -90 cm H 2 O) when compared with a plethysmograph (10). In the present study, reported VTs are the average of ten cycles of inspired and expired volumes, which are distinguished by zero crossings of the flow signal.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations